(Biased) Grading of Students’ Performance: Students’ Names, Performance Level, and Implicit Attitudes - Bonefeld, Meike; Dickhäuser, Oliver (Frontiers in Psychology, 2018)
Biases in pre-service teachers’ evaluations of students’ performance may arise due to stereotypes (e.g., the assumption concerning a lower potential of students with a migrant background). This study examines the effects of migrant background, performance level, and implicit attitudes toward individuals with a migrant background on performance assessment (assigned grades and number of counted errors in dictation). Pre-service teachers (N=203) graded the performance of a student who ostensibly has a migrant background statistically significantly worse than the one of a student without an ostensibly migrant background. The differences were more pronounced when the performance level was poor and the pre-service teachers held relatively positive implicit attitudes toward individuals with a migrant background. Interestingly, concerning the number of counted errors, only performance level had an effect. Results support the assumption of bias in grading students with a migrant background in a 3rd grade level dictation assignment among pre-service teachers.